Isolated abducens nerve palsy in a patient with asymptomatic SARS-CoV-2 infection. (July 2021) - Anilkumar, Aishwarya; Tan, Elizabeth; Cleaver, Jonathan; Morrison, Hamish D.
Highlights: SARS-CoV-2 is associated with a range of neuro-ophthalmological complications. Isolated abducens nerve palsy may be the presenting feature of SARS-CoV-2 infection. We review published cases to date of abducens nerve palsy associated with SARS-CoV-2 infection. Abstract: The neuro-ophthalmological complications of SARS-CoV-2 infection are emerging but the spectrum of presentations and pathophysiological mechanism underpinning the association remains to be fully determined. We describe the case of a 44-year-old female who presented with a 12-hour history of diplopia preceded by a mild headache and found to have an isolated right abducens nerve palsy. Initial vital signs were normal but she developed a fever and nasopharyngeal swab confirmed SARS-CoV-2 infection by RT-PCR. All other investigations returned normal including blood tests, chest X-ray, MRI brain and cerebrospinal fluid analysis. She remained systemically well, and there was complete resolution of the abducens palsy and diplopia at two week follow up. In the absence of an alternative underlying cause or risk factors identified, the aetiology was presumed to be microvascular and potentially related to the viral infection. We add to the evolving literature of neuro-ophthalmological associations of SARS-CoV-2, discuss possible causal mechanisms and suggest considering asymptomatic SARS-CoV-2 infection in cases of isolated abducens palsy without clear risk factors.